2014
DOI: 10.2967/jnumed.114.143628
|View full text |Cite
|
Sign up to set email alerts
|

Anti-1-Amino-3-18F-Fluorocyclobutane-1-Carboxylic Acid: Physiologic Uptake Patterns, Incidental Findings, and Variants That May Simulate Disease

Abstract: Anti-1-amino-3-18F-fluorocyclobutane-1-carboxylic acid (18F-FACBC) is a synthetic amino acid analog PET radiotracer undergoing clinical trials for the evaluation of prostate and other cancers. We aimed to describe common physiologic uptake patterns, incidental findings, and variants in patients who had undergone 18F-FACBC PET. Methods Sixteen clinical trials involving 611 18F-FACBC studies from 6 centers, which included dosimetry studies on 12 healthy volunteers, were reviewed. Qualitative observations of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 28 publications
5
115
0
Order By: Relevance
“…Some encouraging clinical reports about FACBC are found in the literature (32,33). Recently, investigators reported that FACBC PET/ CT had considerably higher accuracy and helped detect more prostatic and extraprostatic disease than indium 111 ( 111 In)−labeled capromab pendetide, an antibody directed against the internal epitope of the PSMA molecule and imaged with single photon emission computed tomography (SPECT), as discussed later in this article (34). An example of FACBC PET/MR imaging is given in Figure 7.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Some encouraging clinical reports about FACBC are found in the literature (32,33). Recently, investigators reported that FACBC PET/ CT had considerably higher accuracy and helped detect more prostatic and extraprostatic disease than indium 111 ( 111 In)−labeled capromab pendetide, an antibody directed against the internal epitope of the PSMA molecule and imaged with single photon emission computed tomography (SPECT), as discussed later in this article (34). An example of FACBC PET/MR imaging is given in Figure 7.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Benign and malignant bone lesions (e.g. osteoid osteoma and multiple myeloma) have reported uptake (48). Finally, single pelvic, non-focal, or non-mass-like 18F-fluciclovine activity not associated with a CT abnormality in our experience has been uncommonly seen with benign follow-up and should therefore be considered equivocal, warranting further evaluation with MR or biopsy (Fig.…”
Section: Image Interpretationmentioning
confidence: 86%
“…Several benign conditions can demonstrate increase 18F-fluciclovine uptake leading to false-positive findings (48). Benign prostatic hypertrophy, acute and chronic inflammation (including post radiation) and infection all demonstrate varying levels of 18F-fluciclovine uptake.…”
Section: Image Interpretationmentioning
confidence: 99%
“…2). Brain parenchyma activity is minimal, and in most patients, bladder activity is absent or mild (43). Compared with 11 C-MET, 18 F-fluciclovine seems to have more rapid pancreatic clearance and comparatively lower levels of renal and bladder activity.…”
Section: Synthetic or Non-naturally Occurring Pet Radiotracersmentioning
confidence: 98%
“…Industry-sponsored phase 3b trials in the United States and the United Kingdom are ongoing. In our experience, 18 F-fluciclovine PET may be most useful for the detection of small and borderline nodes in the range of 5-15 mm and for occult skeletal lesions not detected by conventional imaging, with a lower sensitivity for blastic skeletal lesions than for mixed and lytic or silent lesions (43).…”
Section: Comparison With Choline For Detection and Restaging Of Recurmentioning
confidence: 99%